2007
DOI: 10.1038/sj.ki.5001955
|View full text |Cite
|
Sign up to set email alerts
|

Very low protein diet supplemented with ketoanalogs improves blood pressure control in chronic kidney disease

Abstract: Blood pressure (BP) is hardly controlled in chronic kidney disease (CKD). We compared the effect of very low protein diet (VLPD) supplemented with ketoanalogs of essential amino acids (0.35 g/kg/day), low protein diet (LPD, 0.60 g/kg/day), and free diet (FD) on BP in patients with CKD stages 4 and 5. Vegetable proteins were higher in VLPD (66%) than in LPD (48%). LPD was prescribed to 110 consecutive patients; after run-in, they were invited to start VLPD. Thirty subjects accepted; 57 decided to continue LPD; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 46 publications
(51 reference statements)
2
92
0
4
Order By: Relevance
“…The content of cholesterol in the VLpD and LpD diets was 60-80 and 90-130 mg/day, respectively. The daily salt amount was almost 2 g higher in LpD than VLpD (i.e., in the diet containing 2300 Kcal, which was the most frequently prescribed, the whole sodium content was 1260 mg/day [53 mEq=3.1 g NaCl] and 540 mg/day [22 mEq=1.3 g NaCl], respectively, in LpD and VLpD diets) (14,15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of cholesterol in the VLpD and LpD diets was 60-80 and 90-130 mg/day, respectively. The daily salt amount was almost 2 g higher in LpD than VLpD (i.e., in the diet containing 2300 Kcal, which was the most frequently prescribed, the whole sodium content was 1260 mg/day [53 mEq=3.1 g NaCl] and 540 mg/day [22 mEq=1.3 g NaCl], respectively, in LpD and VLpD diets) (14,15).…”
Section: Methodsmentioning
confidence: 99%
“…As an additional difference, the two diets contained a different percentage of vegetable proteins that was equal to 48% in LpD and 66% in VLPD (14,15).…”
Section: Methodsmentioning
confidence: 99%
“…12 In addition, excessive sodium intake is thought to have direct toxic effects on blood vessels through mediating factors such as oxidative stress, inflammation, endothelial cell dysfunction, and vascular stiffness. [13][14][15] The available evidence detailing the effects of sodium restriction in CKD patients is of poor quality, lacks randomization, [16][17][18] a control group, 17 or blinding, 10,11 or does not use gold-standard measurement techniques (e.g., using clinic instead of ambulatory BP). 10,11 Furthermore, several studies failed to either evaluate or adjust for the influence of key confounding factors, such as potassium intake or body weight, 10,11,[19][20][21][22] thereby making it difficult to assess whether the observed results can be solely attributed to dietary sodium.…”
mentioning
confidence: 99%
“…[19] In a recent prospective, non-randomized study in which 110 consecutive patients with stages 4 and 5 CKD were followed for six months, Bellizzi et al compared the effects of three different types of diet on blood pressure levels. [10] The authors have shown that the keto diet (0.35 g protein/kg b.w. per day) induced a significant decrease of blood pressure (14 mm Hg on average in systolic values) associated with the reduction of antihypertensive drugs.…”
Section: Effect Of Renal Diets On CV Risk Factors Hypertensionmentioning
confidence: 99%
“…Among the latter, nutritional treatment may have a central role. [9] As a matter of fact, among the different goals of dietary prescription in CKD patients, such as the protection of residual renal function and delay of dialysis initiation time, the prevention and correction of complications of renal failure [9,10] especially those favoring the development of CV complications-have a major importance because CV disease plays a major role in the long-term prognosis of CKD patients. Unfortunately, very few high quality studies have addressed the effect of dietary management implemented in CKD patients on the overall risk of cardiovascular events, [11,12] but some data could be extrapolated from the literature regarding the known CV risk factors It is commonly believed that the diet for renal patients mainly consists of a restriction in protein intake.…”
Section: A Cupisti Et Almentioning
confidence: 99%